2017
DOI: 10.1248/bpb.b17-00524
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Protects Bone Marrow-Derived Mesenchymal Stem Cells against Hydrogen Peroxide-Induced Apoptosis through PI3K/Akt and ERK1/2 Pathways

Abstract: Bone marrow-derived mesenchymal stem cells (BMSCs) transplantation is one of the new therapeutic strategies for treating ischemic stroke. However, the poor survival rate of transplanted BMSCs in ischemic tissue limits the therapeutic efficacy of this approach. Oxidative stress is a major mechanism underlying the pathogenesis of brain ischemia and has a negative impact on the survival of transplanted BMSCs. Tetramethylpyrazine (TMP) has been reported to possess potent antioxidant activity. In the present study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 31 publications
(37 reference statements)
1
16
0
Order By: Relevance
“…Its promote neural progenitor/precursor cells migration (Kong et al 2016) and protects neurons from oxygen–glucose deprivation-induced death (Shao et al 2017). TMP also protects bone marrow-derived mesenchymal stem cells against H 2 O 2 -induced apoptosis by regulating the PI3K/Akt and ERK1/2 signalling pathways (Fang et al 2017; Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Its promote neural progenitor/precursor cells migration (Kong et al 2016) and protects neurons from oxygen–glucose deprivation-induced death (Shao et al 2017). TMP also protects bone marrow-derived mesenchymal stem cells against H 2 O 2 -induced apoptosis by regulating the PI3K/Akt and ERK1/2 signalling pathways (Fang et al 2017; Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an increasing amount of evidence indicates that TMP exerts anticerebral ischemia effects both in vivo and in vitro. Various mechanisms have been suggested to underlie the activities of TMP, including the activation of free radical scavenging [35,36], the inhibition of Ca 2+ overload [35], the maintenance of mitochondrial function [35], the suppression of apoptosis [37,38] and inflammation [23,39], and the stimulation of neuronal differentiation [40]. Current in vivo results have shown that treating with TMP can significantly reduce brain infarction, behavioral functional impairment, and cerebral water content [32,33,35,39,41] in rats with middle cerebral artery occlusion-(MCAO-) induced cerebral ischemia.…”
mentioning
confidence: 99%
“…Bone marrow-derived mesenchymal stem cells (BMSCs) pretreated with TMP (10, 25, 50, 100, and 200 μmol•L -1 ) for 24 h and then exposed to 500 μmol•L -1 H 2 O 2 for 24 h exhibited significantly increased viability and decreased apoptosis and ROS generation. Furthermore, the protective effects of TMP were related to increased Bcl-2 expression, attenuated Bax expression, and 3 Oxidative Medicine and Cellular Longevity 5 Oxidative Medicine and Cellular Longevity enhanced levels of phosphorylated AKT (p-AKT) and p-ERK1/2 [37].…”
mentioning
confidence: 99%
“…Other studies indicated that AKT signaling is involved in the regulation of MSC survival, proliferation, differentiation, apoptosis, and migration. [22][23][24]37,38 Wu T et al noted that activation of PTEN/AKT signaling further activates NF-κB to promote TGFβ1 expression, thereby enhancing the immunosuppressive capacity of MSCs. 39 We hypothesized that CMA also regulates the activity of the AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory factor-stimulated AKT activation mediates CMA inhibition AKT signaling has been widely investigated in the proliferation, differentiation, and survival of MSCs, [22][23][24] but few reports have shown whether AKT signaling participates in the regulation of MSC immunosuppression. We found that the phosphorylation level of AKT at Ser473 and Thr308 increased following IFN-γ plus TNF-α stimulation with time ( Fig.…”
Section: Cma Negatively Regulates Inos Expression In Mscsmentioning
confidence: 99%